Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s00394-015-1118-4
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and oxidative stress response to selenium yeast in the non-smoking individuals: a short-term supplementation trial with respect to GPX1 and SEPP1 polymorphism

Abstract: PurposeSelenium, both essential and toxic element, is considered to protect against cancer, though human supplementation trials have generated many inconsistent data. Genetic background may partially explain a great variability of the studies related to selenium and human health. The aim of this study was to assess whether functional polymorphisms within two selenoprotein-encoding genes modify the response to selenium at the level of oxidative stress, DNA damage, and mRNA expression, especially in the individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 54 publications
0
15
1
Order By: Relevance
“…As for the influence of diet, none of the individuals reported a change to his/her dietary habits during the trial. The second major weakness of this study is attributable to the fact that the trial was not randomized (subjects were selected for the study according to genotype) and not placebo controlled (for details see [22]). Since no separate control group was investigated, we compared all data with respect to baseline values, measured on the first day of the trial, before taking the first pill with the supplement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As for the influence of diet, none of the individuals reported a change to his/her dietary habits during the trial. The second major weakness of this study is attributable to the fact that the trial was not randomized (subjects were selected for the study according to genotype) and not placebo controlled (for details see [22]). Since no separate control group was investigated, we compared all data with respect to baseline values, measured on the first day of the trial, before taking the first pill with the supplement.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the trial, as well as subjects’ exclusion criteria, were described elsewhere [22]. The exclusion criteria for subjects’ recruitment included inter alia current smoking and self-reported prevalence of diabetes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, human studies have failed to demonstrate an association between Se status and selenoprotein transcripts [14][15][16] . Only three studies have observed a positive association between Se supplementation and increased selenoprotein expression in humans (SELENOF, SELENOK, GPX1 and SELENOP) 13,17,18 .…”
Section: Introductionmentioning
confidence: 99%